The Influence of Leverage, Profitability, and Company Size With Moderation of Audit Quality on Company Value - Kinanti, Kartika Ayu; Rusdianti, Imanita Septian; Septiani, Ria; Mudjiyanti, Rina; Cahyaningati, Retno (Bulletin of Management and Business, 2024)
Companies in the D222 sector in Indonesia have the potential to dominate the global market. This study aims to examine how the value of companies in the D222 sector is formed by financing policies, namely leverage, the ability to generate profits, namely profitability. Additionally, this research also investigates the influence of company size on firm value. The urgency of this research is underscored by the fact that audit performance is instrumental in driving strategic efforts by companies to enhance their value. Sampled from the years 2020-2022 and drawn from companies listed on the stock exchange, the population consists of 26 companies. Purposive sampling was employed to select a sample of 19 companies in the D222 sector. The data was analyzed using multiple regression in SPSS version 27. The findings indicate that financing policies, specifically Leverage, do not significantly influence firm value, whereas the ability to generate profits, namely Profitability, has a significant positive impact on firm value. Company size does not appear to affect the increase in firm value. However, the role of Audit Quality as a moderator yields varying results. Regarding the relationship between financing policies, namely leverage, and firm value, Audit Quality does not seem to strengthen it. The same results are obtained concerning the relationship between the ability to generate profits, namely profitability, and firm value. However, Audit Quality appears to strengthen the relationship between Company Size and Firm Value. These findings offer valuable insights into the interaction of these factors in the context of the processed food industry in Indonesia, aiming for dominance in the global market.